EVALUASI BRANDING KOTA PAYAKUMBUH SEBAGAI KOTA RENDANG - Syarif Hidayatullah; Ma’ruf; Verinita (Halu Oleo University, 2024)
This study focused to find out the relationship among several aspects such as attitude toward the brand, brand image, brand equity, and brand preference. By using a quantitative approach and online questionnaires were distributed to 143 tourists who had visited the city of Payakumbuh as Kota Rendang in the last 5 years. A purposive sampling technique with several criteria was used to separate unqualified participants, and then the data was analyzed with the Structural Equation Modeling - Partial Least Square (SEM-PLS) technique by assisting Smart-PLS Software's latest version. The result shows that all research expectations are met.